Estrategias didácticas para el ámbito de comprensión y expresión artística para primer grado de educación general básica en la escuela Misión Andina - Bonilla Junta, Lucy Yonela (2018)
Through this research, we seek to create teaching materials for the field of understanding and artistic expression of the first grade of basic general education at the Misión Andina School in order to improve learning in different areas through art and culture. Empowering our attachment to different techniques that seek the same goal that is to achieve optimal results in the teaching-learning process. Teachers are looking for new methods of help every day so that students can obtain meaningful learning and are in accordance with their context of life, maintaining their attachment to culture and identity, however many of the teachers are accustomed to clearly follow the curriculum. without realizing the place where they are offering the cathedra, leaving aside the cultural theme and the worldview of their students, without realizing that art and culture go hand in hand and through them, more previous knowledge will achieve the desired end. The work is divided into two phases the first; observation through the visit to the school will seek to find the deficiencies in which you can provide support to improve the process, with the result of non-participant observation will have the basis for the second phase that is production of teaching materials that will be implemented in the mentioned educational institution, thus demonstrating its effectiveness in the study process.